The Reflection Of Women Emancipation In Fatima Mernissi's Dream Of Trespass (1994): A Feminist Analysis - Bayhaqi, Muvid (2012)
This study is aimed to show the conditions of women emancipation in Morocco, especially in the harem life by using feminist approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the reflection of women emancipation by using feminist approach. The result of the analysis will answer the problem statement. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is the Dream of Trespass novel written by Fatima Mernisssi in 1994. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. Firstly, based on the structural analysis, it is indicated that each of narrative elements of the novel is related one and each other. Secondly, the novel illustrates that women emancipation in the harem is mostly ignored. The women live with many rules and restrictions from the men in many aspects of life in the harem.